Patients' narratives of their patient participation in the myocardial infarction pathway. (31st January 2019) - Bårdsgjerde, Elise Kvalsund; Kvangarsnes, Marit; Landstad, Bodil; Nylenna, Magne; Hole, Torstein
Abstract: Aim: To explore how patients in areas without local percutaneous coronary intervention (PCI) facilities experience patient participation in different phases of the myocardial infarction pathway. Background: Acute treatment of myocardial infarction often involves PCI. In Norway, this treatment is centralized at certain hospitals; thus, patients often require long‐distance transportation and experience frequent hospital transfers. Short hospital stays, transfers between hospitals and the patient's emotional state pose challenges to promoting patient participation. Design: A qualitative design with a narrative approach. Methods: Participants were recruited through purposive sampling. Eight men and two women were interviewed in 2016. Findings: Four themes related to the patients' experiences at the beginning, middle and end of the pathway were identified: (a) Lack of verbal communication in the acute phase; (b) trust in healthcare professionals and treatment; (c) lack of participation and coordination at discharge; and (d) shared decision‐making in rehabilitation. The findings showed how the patients moved from a low level of patient participation in the acute phase to a high level of patient participation in the rehabilitation phase. Conclusion: This is the first study to explore patient participation in different phases of the myocardial infarction pathway. We argue that individual plans for information and patient participation are important to improve patient involvement in an earlier stage of the pathway. Further research from a healthcare professional perspective can be valuable to understand this topic. Impact: This study gives new insight that can be valuable for healthcare professionals in implementing patient participation throughout the pathway. Abstract : 目的: 探讨没有局部经皮冠状动脉介入治疗设施的地区的患者在心肌梗死过程不同阶段的参与情况。 背景: 急性心肌梗死的治疗通常包括皮冠状动脉介入治疗。在挪威, 这种治疗集中在某些医院;因此, 患者往往需要长途交通, 并经历频繁的医院转诊。短时间的住院、医院间的转诊和病人的情绪状态对促进病人参与带来了挑战。 设计: 定性设计与叙述方法 方法: 参与者是通过有目的的抽样招募的。2016年, 共有8名男性和2名女性接受了采访。 研究结果: 确定了患者在过程开始、中间和结束时的经历相关的四个主题:(a)急性期缺乏口头交流;(b)信任保健专业人员和治疗;(c)出院时缺乏参与和协调;(d)在康复方面的共同决策。 研究结果显示了患者如何从急性期的低水平患者参与转变为康复期的高水平患者参与。 结论: 这是第一个探索心肌梗死过程不同阶段患者参与的研究。我们认为, 个人的信息计划和患者的参与对提高患者在路径早期阶段的参与很重要。从卫生保健专业人员的角度进行进一步的研究, 有助于理解这一主题。 影响: 这项研究提供了新的见解, 对于医疗保健专业人员实施全程患者参与具有重要价值。